Development of a bile acid-based newborn screen for Niemann-Pick disease type C - Jiang, Xuntian; Sidhu, Rohini; Mydock-McGrane, Laurel; Hsu, Fong-Fu; Covey, Douglas F.; Scherrer, David E.; Earley, Brian; Gale, Sarah E.; Farhat, Nicole Y.; Porter, Forbes D.; Dietzen, Dennis J.; Orsini, Joseph J.; et al. (Science translational medicine, 2016)
Expanding the newborn screen - Niemann-Pick disease type C (NPC) is a fatal neurologic disorder caused by the deficiency of an enzyme involved in cholesterol storage. Although this disease was untreatable in the past, new therapeutics are now in clinical trials, but they are most likely to be effective if treatment is started as early as possible, before neurodegeneration has occurred. Jiang et al. identified three bile acids that are greatly increased in the blood of patients with NPC compared to healthy controls. The authors also demonstrated that one of these bile acids can be reliably measured in dried blood spots using mass spectrometry, suggesting that this bile acid test should be evaluated for potential addition to neonatal screening programs. - Niemann-Pick disease type C (NPC) is a fatal, neurodegenerative, cholesterol storage disorder. With new therapeutics in clinical trials, it is imperative to improve diagnostics and facilitate early intervention. We used metabolomic profiling to identify potential markers and discovered three unknown bile acids that were increased in plasma from NPC but not control subjects. The bile acids most elevated in the NPC subjects were identified as 3β,5α,6β-trihydroxycholanic acid and its glycine conjugate, which were shown to be metabolites of cholestane-3β,5α,6β-triol, an oxysterol elevated in NPC. A high-throughput mass spectrometry-based method was developed and validated to measure the glycine-conjugated bile acid in dried blood spots. Analysis of dried blood spots from 4992 controls, 134 NPC carriers, and 44 NPC subjects provided 100% sensitivity and specificity in the study samples. Quantification of the bile acid in dried blood spots, therefore, provides the basis for a newborn screen for NPC that is ready for piloting in newborn screening programs. - A newborn screen for Niemann-Pick disease type C was developed on the basis of discovery of a bile acid marker. - A newborn screen for Niemann-Pick disease type C was developed on the basis of discovery of a bile acid marker.
Gesehen am 06.05.2020